2016
DOI: 10.1021/acs.jpcc.6b08450
|View full text |Cite
|
Sign up to set email alerts
|

Cartesian Decomposition of Infrared Spectra Reveals the Structure of Solution-Deposited, Self-Assembled Benzoate and Alkanoate Monolayers on Rutile (110)

Abstract: Cartesian polarization analysis transforms a set of surface infrared spectra obtained in different geometries into their Cartesian components using a mathematical transform, providing direct insight into the bonding geometry of adsorbed molecules. This technique was extended to uniaxial substrates and used to analyze solution-deposited, self-assembled benzoate and alkanoate monolayers on rutile (110). This analysis resolved a long-standing controversy regarding the existence of paired molecules in benzoate mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…For example, Figure 5 Infrared Spectroscopy Confirms Benzoate Formation. The infrared spectra of benzoate-terminated anatase (001) nanocrystals were strikingly similar to spectra of benzoateterminated rutile (110), 25,26,39 a system in which benzoate is known to bond in a vertical, bridged bidentate geometry. The observed modes are summarized in Table 1 and discussed in the following.…”
Section: ■ Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, Figure 5 Infrared Spectroscopy Confirms Benzoate Formation. The infrared spectra of benzoate-terminated anatase (001) nanocrystals were strikingly similar to spectra of benzoateterminated rutile (110), 25,26,39 a system in which benzoate is known to bond in a vertical, bridged bidentate geometry. The observed modes are summarized in Table 1 and discussed in the following.…”
Section: ■ Resultsmentioning
confidence: 68%
“…As a result, all in-planepolarized spectra are identical on anatase (001), whereas there are two distinct in-plane polarizations (i.e., x and y) on rutile The rutile data are from refs. 25,26,39 The (110). Because of this higher symmetry and the multilayer TiO 2 /SrTiO 3 /TiO 2 substrate, we were unable to use the Cartesian transformation techniques 39 that enabled the resolution of two additional C−H stretch modes at 3056 and 3070 cm −1 on benzoate-terminated rutile (110).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The Ti, O, and H atoms are represented by blue, red, and white spheres, respectively. See ref for more information.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, benzoic acid, the simplest analogue of the dyes used in TiO 2 -based dye-sensitized solar cells, binds to TiO 2 (110) as benzoate in two nearly isoenergetic isomers 8 as shown in Figure 1. The H atoms produced in this dissociative adsorption reaction bind to surface "bridging" O atoms, forming hydroxyls.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Whereas alkanoic acids have been studied along with thiols and silanes since the emergence of the field of self-assembled monolayers (SAMs), corresponding investigations of SAMs formed from aromatic carboxylic acids (ArCAs), either in an ultrahigh vacuum environment or at the liquid/solid interface, have been rather scarce. Spectroscopic studies showed that layers with a well-defined orientation of the molecules can be formed through coordinative bonding of the carboxylate moiety to the substrate, and more recent experiments employing scanning tunneling microscopy (STM) further revealed that ArCA SAMs form highly crystalline layers both on metals, such as Ag and Cu, and on metal oxides, such as TiO 2 . …”
Section: Introductionmentioning
confidence: 99%